Kesantunan Berbahasa Jawa Ragam Krama pada Tuturan TikTok @agilnofian: Analisis Prinsip Leech dalam Perspektif Wijana - Kinanti Raraswanti; Endang Kurniati; Eka Yuli Astuti (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Javanese is a language that is synonymous with politeness. In fact, it was found that the use of Javanese language was a variety of manners that did not reflect politeness in @agilnofian TikTok videos. This study aims to analyze compliance with and violation of Leech's principle of politeness in the register of Javanese krama in @agilnofian TikTok video uploads. This study uses a qualitative approach with a descriptive method. The research data is in the form of Javanese speech in a variety of manners in @agilnofian TikTok video uploads that contain elements of linguistic politeness. The data source is in the form of all speech in 150 TikTok video uploads @agilnofian the period October 2024-December 2025. Data was collected by the observation method and the advanced recording technique. The data analysis technique of this study uses the Miles & Huberman interactive model with four stages, namely, data collection, data condensation, data presentation, and conclusions/verification. The results of the study showed that Javanese speech of various manners on TikTok @agilnofian more impolite than polite ones. Compliance with the principle of language politeness in TikTok speech was @agilnofian found as much as 48%, while violations of the principle of language politeness were found as many as 52%. The maxim that is most followed is the maxim of wisdom, while the maxim that is violated the most is the maxim of praise. The dominance of violations of the principle of language politeness in this study has implications for the shift in the function of using the Javanese language from a marker of respect and politeness to a means of expression of humor and entertainment on social media. Thus, the existence of this research is expected to be an input so that the Javanese language is used properly and still pays attention to the value of language politeness, especially when communicating on social media.